A Monthly Analysis of Road Traffic Accident in Selected Local Government Areas of Lagos State, Nigeria - Atubi, Augustus .O. (Richtmann Publishing, 2012)
This study examined monthly analysis of road traffic accidents in selected Local Government Areas of Lagos State,Nigeria and to suggest preventive and corrective safety measures towards reducing road traffic accidents in the study area.Using accident records from the Nigerian Police Force and Federal Road Safety Commission for the thirty two (32) years periodfrom 1970 – 2001, this study seeks to reveal the traffic situation and accident pattern on monthly basis in 9 Local GovernmentAreas of Lagos State, Nigeria. Further observation revealed that the most accident prone Local Government Areas (LGAs) areLagos Island, Lagos Mainland, Ajeromi/Ifelodun, Ikeja, Oshodi/Isolo, Apapa, Eti-Osa, Kosote and Ojo. Thus, these are the LGAsthat deserve urgent traffic accident mitigation attention e.g. intensified policing by the road safety corps. Again, for variousreasons, it was also observed that most of the accidents in Nigeria occur in the months of June, July, September, October,November and December. June, July and September are the peak rainy months and more road accidents occur in rainy monthsbecause wet road conditions affect many drivers’ ability to see and be seen. Based on the findings, recommendations wereproffered on how to reduce the phenomenon of road traffic accidents in Lagos State, Nigeria.